Calcium hydroxyapatite in orofacial harmonization: a narrative review of the literature (Research, Society and Development, 2023)
The demand for healthy, flawless, youthful-looking, wrinkle-free skin is currently increasing. As a result, there is a greater demand for aesthetic procedures in society, as well as the need for innovation and new methods for applying facial harmonization techniques. In this context, calcium hydroxyapatite emerged as a suitable biostimulator to meet current aesthetic demands. Calcium hydroxyapatite is a synthetic compound composed of microspheres suspended in an aqueous gel. Furthermore, it is a biocompatible material, does not cause allergic reactions, is opaque and naturally degrades. This makes it a viable option for facial rejuvenation and harmonization treatment. The objective is to provide a safe, simple and satisfactory harmonization for the individual, resulting in the desired effects. The objective of this research is, through a narrative review of the literature, to offer the specialist in orofacial harmonization the application of calcium hydroxyapatite in the specialty.